Explanation and interpretation of three unclear words in Bavli Eruvin 104a-b - Zur, Uri (HTS teologiese studies, 2022)
This article engages in the explanation and interpretation of three unclear words, dyofe, meiarak and kitana, that appear in the Babylonian Talmud, Tractate Eruvin 104a–b. The words are part of the Talmudic text and the article addresses the various meanings ascribed to them and explains them. This is required because of the contradiction and confusion that exist in the explanation and interpretation of these three words. The research method employed involves examining the various explanations given by the commentators, comparing the words with other sources and checking their suggested meanings in Talmudic dictionaries. The research results show different versions of these three words and the conclusions indicate that the different versions change their possible explanation and interpretation.Contribution: The innovation of this article is in presenting the various sources of these words, noting their various versions and the different interpretations that derive from them. The article also describes the interpretive development of these words, as well as noting the commentators who offer explanations for the two first words, which generate contradictory meanings.